Evaluation of salivary interleukin-6 in children with early childhood caries after treatment - Medhini Madhavan Menon; R Varma Balagopal; Krishnan Sajitha; Kumaran Parvathy; G Bhat Sangeetha; X Mamachan Arun; Janardhanan Sureshkumar (Wolters Kluwer Medknow Publications, 2016)
Background: The role of cytokines as a marker in the oral inflammatory process in ECC has not been fully explored before and after full mouth rehabilitation. Aims: The aim of this study was to assess the level of salivary interleukin-6 (IL-6) in children with ECC and to compare its levels before and after comprehensive full mouth rehabilitation. Methods and Materials: Saliva samples were collected from children with ECC prior to dental treatment and 3-month post treatment. The salivary IL-6 levels were analyzed using the ELISA method. The gingival index was also timely recorded. Oral health awareness sessions were conducted for children and their parents at regular intervals during the 3-month study period. Statistical analysis used: Wilcoxon Signed Rank test compared the levels of salivary IL-6 while, the paired t test compared the values of gingival index before and after treatment. Results: The mean level of salivary IL-6 before and 3 months after treatment had reduced and this reduction was statistically significant (P< 0.000). The gingival index scores had also reduced significantly 3-months post treatment (P< 0.002). Conclusions: Children with ECC when completely rehabilitated and kept under frequent follow up, which includes reinforcement of oral hygiene measures and maintaining a low caries activity state, the level of inflammation (IL-6) can definitely be minimized and thereby improving the quality of life of affected children.